PENGARUH METODE ROLE PLAY DAN MOTIVASI BELAJAR TERHADAP HASIL PRESTASI BELAJAR MAHASISWA DALAM MATA KULIAH ASUHAN KEBIDANAN I DI AKADEMI KEBIDANAN BHAKTI PUTRA BANGSA PURWOREJO - FETTY CHANDRA WULANDARI (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2013)
Fetty Chandra Wulandari, S541102029. 2012. The Effect of Role Play and Learning Motivation on the Learning Achievement of Midwifery Care I throughout Kedu Ex- Residency (A Study on Purworejo Bakti Putra Bangsa Midwifery Academy). Thesis: First Counselor Commission: Prof. Dr. Sunardi M.Sc. Second Counselor: Putu Suriyasa, dr, MS, PKK, Sp.Ok. Family Medical Magister Study Program of Postgraduate Program of Surakarta Sebelas Maret University. This research aims to analyze the effect of Role Play method and learning motivation on the Learning Achievement of Midwifery Care I in Purworejo Bakti Putra Bangsa Midwifery Academy. This study was a quasi-experiment research. The population was the second semester students selected using Cluster Random Sampling and obtained from the Purworejo Bakti Putra Bangsa Midwifery Academy, consisting of 50 students. 25 students obtained conventional method + Role Play and 25 students obtained conventional method. The data was collected from the academic division to obtain the value of learning achievement, while the data of learning motivation was obtained by distributing questionnaire, the items of whichhad been tested for their validity and reliability. The data analysis was processed using a twoway Analysis of Variance (ANOVA) or two factorial design. The result of research showed probability value (p value) of 0.023 < 0.05, so there was a positive significant effect of Role Play method and learning achievement on the Learning Achievement of Midwifery Care I in Purworejo Bakti Putra Bangsa Midwifery Academy.